Modulation of action potential and calcium signaling by levetiracetam in rat sensory neurons - Ozcan, Mete; Ayar, Ahmet (Taylor & Francis Ltd, 2012)
Levetiracetam (LEV), a new anticonvulsant agent primarily used to treat epilepsy, has been used in pain treatment but the cellular mechanism of this action remains unclear. This study aimed to investigate effects of LEV on the excitability and membrane depolarization-induced calcium signaling in isolated rat sensory neurons using the whole-cell patch clamp and fura 2-based ratiometric Ca2+-imaging techniques. Dorsal root ganglia (DRG) were excised from neonatal rats, and cultured following enzymatic and mechanical dissociation. Under current clamp conditions, acute application of LEV (30 mu M, 100 mu M and 300 mu M) significantly increased input resistance and caused the membrane to hyperpolarize from resting membrane potential in a dose-dependent manner. Reversal potentials of action potential (AP) after hyperpolarising amplitudes were shifted to more negative, toward to potassium equilibrium potentials, after application of LEV. It also caused a decrease in number of APs in neurons fired multiple APs in response to prolonged depolarization. Fura-2 fluorescence Ca2+ imaging protocols revealed that HiK(+) (30 mM)-induced intracellular free Ca2+ ([Ca2+](i)) was inhibited to 97.8 +/- 4.6% (n = 17), 92.6 +/- 4.8% (n = 17, p < 0.01) and 89.1 +/- 5.1% (n = 18, p < 0.01) after application of 30 mu M, 100 mu M and 300 mu M LEV (respectively), without any significant effect on basal levels of [Ca2+](i). This is the first evidence for the effect of LEV on the excitability of rat sensory neurons through an effect which might involve activation of potassium channels and inhibition of entry of Ca2+, providing new insights for cellular mechanism(s) of LEV in pain treatment modalities.
Keywords: Levetiracetam; antiepileptic drug; dorsal root ganglion; pain; action potential; calcium imaging